Thermodynamic properties of ternary mixtures containing 1-ethyl-3-methylimidazolium tetrafluoroborate with cyclic amides and cyclopentanone or cyclohexanone at T = (293.15, 298.15, 303.15 and 308.15) K. (July 2015) - Sharma, V.K.; Kataria, J.; Solanki, S.
Graphical abstract: Densities, ρ ijk for 1-ethyl-3-methylimidazolium tetrafluoroborate (i) + 1-methyl pyrrolidin-2-one (j) + cyclopentanone (k) mixture at T  = (298.15, 293.15, 303.15 and 308.15) K. Highlights: The measured ρ ijk and u ijk data of the studied mixtures have been used to determine V ijk E and κ S E ijk . The V ijk E and κ S E ijk data have been fitted to Redlich–Kister equation. The V ijk E and κ S E ijk data has been analyzed in terms of Graph and PFP theories. It has been observed that Graph theory describe well the V ijk E and κ S E ijk values. Abstract: The density, ρ ijk and speed of sound, u ijk of ternary {1-ethyl-3-methylimidazolium tetrafluoroborate (i) + pyrrolidin-2-one} or {1-methyl pyrrolidin-2-one (j) + cyclopentanone or cyclohexanone (k)} mixtures have been measured at temperatures (293.15, 298.15, 303.15, 308.15) K. The excess molar volume, V ijk E and excess isentropic compressibility, κ S E ijk (obtained by employing density and speed of sound data) have been fitted to Redlich–Kister equation to determine ternary adjustable parameters along with their standard deviations. The V ijk E and κ S E ijk results have been tested in terms of Graph and Prigogine–Flory–Patterson (PFP) theories. The results indicate that V ijk E and κ S E ijk values calculated by Graph theory are comparable to the experimental values.